MALDI‐MSI for the analysis of a 3D tissue‐engineered psoriatic skin model. Issue 11 (15th June 2016) - Harvey, Amanda; Cole, Laura M.; Day, Rebecca; Bartlett, Maggie; Warwick, John; Bojar, Richard; Smith, David; Cross, Neil; Clench, Malcolm R.
Abstract : MALDI‐MS Imaging is a novel label‐free technique that can be used to visualize the changes in multiple mass responses following treatment. Following treatment with proinflammatory cytokine interleukin‐22 (IL‐22), the epidermal differentiation of Labskin, a living skin equivalent (LSE), successfully modeled psoriasis in vitro. Masson's trichrome staining enabled visualization and quantification of epidermal differentiation between the untreated and IL‐22 treated psoriatic LSEs. Matrix‐assisted laser desorption ionization mass spectrometry imaging was used to observe the spatial location of the psoriatic therapy drug acetretin following 48 h treatments within both psoriatic and normal LSEs. After 24 h, the drug was primarily located in the epidermal regions of both the psoriatic and nonpsoriatic LSE models whereas after 48 h it was detectible in the dermis.